THE INFLUENCE OF SERVICE QUALITY AND PROMOTION ON CONSUMER PURCHASE DECISIONS OF CARDINAL JEANS: (Case Study at the Yogya Mall Keuntungan Department Store) - Evan Pahruri; Gian Fitralisma; Nur Afridah (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
Abstract This study aims to determine the effect of service quality and promotion on consumer purchasing decisions of cardinal jeans (Studi Toserba Yogya Mall Keuntungan), The population in this study were 1652 consumers. The criteria used as samples in this study are consumers who buy cardinal jeans using the slovin formula, so the number of samples is 100 respondents. This type of research is quantitative research. The data collection technique used to analyze is by distributing questionnaires in the form of questionnaires to consumers, the research was carried out using SPSS Version 25.0. The results were analyzed to determine the validity and reliability test, determination test, classical assumption test, multiple linear regression and multiple correlation, f test and t test and coefficient of determination test. Based on the results of this study, it shows that the quality of service and promotion of the purchasing decision of cardinal jeans at the department store of Yogyakarta Mall Keuntungan has a significant influence on the sales of cardinal jeans at the department store Yogya Mall Keuntungan.